Landslide Science for a Safer Geoenvironment Volume 2: Methods of Landslide Studies - Sassa, Kyoji; Canuti, Paolo; Yin, Yueping (Springer International Publishing : Imprint: Springer, 2014)
This volume contains peer-reviewed papers from the Third World Landslide Forum organized by the International Consortium on Landslides (ICL) in June 2014. The complete collection of papers from the Forum is published in three full-color volumes and one mono-color volume. This second full-color volume contains the following:   ·        Physical modeling and material testing ·        Application of numerical modeling techniques to landslides ·        Remote sensing techniques for landslide mapping and monitoring ·        Hazard mapping ·        Monitoring, prediction, and warning of landslides ·        Risk assessment ·        Remedial measures and prevention works ·        Risk reduction strategy ·        Inventory and database.